Psychosocial risks in labour and social security law: a comparative legal overview from Europe, North America, Australia and Japan (Berlin, 2017)
"This book studies a range of legal systems and compares them on their ability to deal with psychosocial risks at work. The topic of psychosocial risks at work has received much attention recently, both from the general public, the press, and those working in the legal arena. It is difficult for lawyers to deal with the issue of psychosocial risks at work due to the multifactorial and subjective features involved. This book presents the views on the subject from leading national and international experts and provides an in-depth coverage of legal systems used in Southern and Northern European countries, as well as Canada and Japan to deal with this topic. The book looks at prevention of psychosocial risks from a labor law perspective and at compensation and reparation from a social security law perspective. It pays special attention to the topic of bullying in the work place, which is currently the subject of most legal summons."